A computer programme for the simulation of water reticulation systems in gold mines - Holton, Mark Collins (My University, 2015)
This report investigates the application of digital computer simulation models to the analysis and optimization of complex mine water reticulation systems- A simulation program is developed and documented, Guidelines in the construction and use of mine water models are applied in a case study of water quality and quantity aspects of Unisel Gold Mine.
Keywords: Gold mines and mining; Mining engineering--Simulation methods